Lempel Ziv Complexity (LZC) and Permutation Entropy (PE) analysis. - Magaly Catanzariti (20865500) (2025)
(A) Comparison of LZC values between dogs without (green) and under the effect of trazodone (red) across across behavioural stages. Analysis was performed for low frequency [1, 16] Hz (left panel) and high frequency [16, 45] Hz (right panel). (B) Similar comparison but using PE analysis with the parameter used D = 4 and . The boxplots show the values averaged over all four recording channels per dog. Statistical analysis between groups was performed using the Wilcoxon signed-rank test for Wakefulness and Drowsiness and Mann-Whitney test for NREM and REM (*p < 0.05, ** p < 0.01).